PROGRAM OF PT TIRTA INVESTAMA (DANONE AQUA) AIRMADIDI ADDRESSING MEA BY EVALUATING THE WELFARE BY USING THE IMPORTANCE AND PERFORMANCE ANALYSIS - Lasut, Stevie A. (Journal of Asean Studies on Maritime Issues, 2017)
Aqua is a brand of packaged water in Indonesia that is produced by PT Aqua Golden Mississippi Tbk since 1973. It is a very well-known brand of packaged water and has become the generic brand of packaged water in Indonesia. The objective of this research is to analyze the importance and performance of Employee Welfare Program in PT Tirta Investama (DanoneÂ  AQUA) Airmadidi. Based on the data analysis this research found that Employee welfare programs that have high importance and low performance or labeled as â€œconcentrate hereâ€ are National Security for the workforce (JAMSOSTEK)/BPJS membership and Economic Enterprise, â€œkeep up the good workâ€ are Outside Workplace Accident Insurance, Life Insurance, Place of Worship and Recreation and employee welfare program that have low importance and low performance or labeled as â€œlow priorityâ€Â  is Sport & Art. Another findings is there is no employee welfare program that have high performance but low importance or labeled as â€œpossible overkillâ€.Keywords: Employee Welfare, Importance Performance Analysis